EMS-45 Tool Steels Hardenability Experiment using Jominy ASTM A255 Test Method - Syamsul Hadi; Eddy Widiyono; Winarto Winarto; Dedy Z. Noor (IPTEK The Journal for Technology and Science, 2013)
Hardenability of steels is an important way to determine heat treatment and material properties that produce component products. Jominy test is one of the method to know hardenability of steels. The Jominy ASTM A255 in used as a method for carriying out and this reseach. Parameter such as austenite temperature, holding time, cooling rate and then the results is dedicated by the prediction result, with Non Linear Numerical Equation Method. Based on test, it’s known, increasing austenite temperature, longer holding time and high cooling rate, will increase hardenability of steels. The different between the results and the prediction result done by Sonh Yue-Peng[15], Matja equation[14] and Zehtab equation[10], about 5 % -10 %. The data obtained from this experiment can be used to determine the appropriated heat treatment in order to get the desired mechanical properties, as well as to avoid distortion.